Word Formation Processes Found on Shopee Live Streaming - Ria Antika; Prihatin Pujiastuti; Ade Fitria Deswita (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
Language is always developing and changing. It can be marked by the emergence of new words or new terms that come from various ways. A very striking development of new terms occurred in the field of commerce. Sellers often choose unique or catchy terms or words to entice buyers to join their live stream. With limited words they can type as their live Shopee title, sellers focus on communicating effectively and efficiently. This study aims to analyze several types of word formation processes found on Shopee Live streaming following the theory from Yule (2006). This research is expected to increase understanding of the word formation process contained in Shopee Live streaming. This research method is descriptive qualitative. Data were taken from written texts; such as titles that appear on Shopee Live Streaming and those performed by different Shopee sellers and then they were analyzed in the form of essays. The texts to be analyzed appear on the top left of the buyer's screen while the streaming is in progress. The findings showed that there were 219 words with a variety of formation processes. Borrowing, which involved 131 data, was the most dominant type used by the sellers. By this research, it is hoped that it can explore something that is developing in the community regarding the phenomenon of the use of new words or the mixing of words from Indonesian with English or with local languages, especially on online marketplace.